Peningkatan Skill dan Pengetahuan Masyarakat tentang Instalasi Panel Surya sebagai Sumber Energi Listrik Alternatif: Increasing the Skill and Knowledge of the Community about Solar Panel Installation as a Source of Alternative Electrical Energy - Ekawita, Riska; Supiyati, Supiyati; Yuliza, Elfi (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2020)
Bengkulu city has abundant solar energy that has not yet been utilized to optimize. Bengkulu people, especially the Muara Bangkahulu district, do not yet have the skills and knowledge to use solar panels to meet their daily electricity needs. In this activity, the workshop was carried out on the use and solar panel installation technique that could be used as an alternative source of electricity. Participants were the residents of RT.20/01, Pematang Gubernur sub-district, Muara Bangkahulu district, Bengkulu City. The workshop consisted of three main parts; they were filling out the questionnaire, presentation, and practice of installing a solar panel. The questionnaire was given at the time before and after the material and practice were done. Some household products that are using solar energy were delivered during the presentation. The next step was the installation practice of solar panels and their components. The questionnaire result shows that participants are attracted to use the solar panel as alternative electric energy. In addition, the community who initially has a limitation of knowledge to install a solar panel, after the workshop is carried out, they have the skill for that installation.